Pengaruh Model Pembelajaran Berbasis Masalah Berbantuan Lembar Kerja Peserta Didik Berbasis Digital (E-LKPD) Terhadap Kemampuan Pemecahan Masalah Matematis Siswa - Azizah, Baiq Hidayatul; Azmi, Syahrul; Kertiyani, Ni Made Intan (FKIP Universitas Mataram, 2025)
This study was motivated by students’ low mathematical problem-solving skills, the lack of innovative learning models, and the limited use of technology in learning media. The purpose of this research is to determine the effect of a problem-based learning model assisted by digital student worksheets on students’ mathematical problem-solving skills. This quasi-experimental research involved all eighth-grade students at one of the junior high schools in mataram city. The sample consisted of class VIII A as the experimental class, which received PBL with digital worksheets, and class VIII B as the control class, which received PBL with printed worksheets. Data were collected using a mathematical problem-solving test and analyzed using a t-test and effect size. The results showed that the use of digital worksheets had a significant effect on students’ mathematical problem-solving skills. The average score of the experimental class increased from 47.75 (pretest) to 70.12 (posttest), while the control class increased from 49.46 to 62.05. The t-test showed that at a 0.05 significance level. The effect size was 0.71, categorized as large, indicating that the applied model and media were effective. This study shows that digital worksheets in problem-based learning can enhance students’ problem-solving skills.